2021
DOI: 10.1007/978-3-030-78354-9_8
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Mastering Uncertainty in Mechanical Engineering

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Pelz (2000) found that PGA (Professional Golfer' Association) players were also affected by putting distance. It was confirmed that the success rate is lowered to 25% at a distance of 10 ft (3.05 m) [9]. Therefore, in this research experiment, the distance was set to 3 m to control the difficulty and to ensure the participants' concentration during the putting task.…”
Section: Introductionmentioning
confidence: 72%
“…Pelz (2000) found that PGA (Professional Golfer' Association) players were also affected by putting distance. It was confirmed that the success rate is lowered to 25% at a distance of 10 ft (3.05 m) [9]. Therefore, in this research experiment, the distance was set to 3 m to control the difficulty and to ensure the participants' concentration during the putting task.…”
Section: Introductionmentioning
confidence: 72%
“…The relationship between raw moments of ξ j and their coefficients P (k) i,j can be written in matrix form (the detail process could be seen in 27,34 ) Other types of uncertainty. Uncertainty mainly includes parameter uncertainty, model uncertainty, observation uncertainty, measure noise [35][36][37] . We have studied the effect of parameter uncertainty on resilience and now we discuss how observation uncertainty affects the resilience of the system.…”
Section: Methodsmentioning
confidence: 99%
“…2. Euler diagram for classification of time-variant and timeinvariant processes, adopted from [2]. is determined to be ν t /h 2 0 with the eddy viscosity ν t and the water depth h 0 .…”
Section: Condition For Quasi-steady Flowmentioning
confidence: 99%
“…It is two-stage since first the design has to be optimised anticipating the operation o(t) and the boundary conditions c(t). This is typical for many engineering problems [2], [8]. While the operation parameter can be adapted after the installation, the design is fixed with construction.…”
Section: Array Optimisationmentioning
confidence: 99%
See 1 more Smart Citation